Modelling and evaluation of aggregate morphology on asphalt compression behavior. (15th February 2017) - Liu, Pengfei; Hu, Jing; Wang, Dawei; Oeser, Markus; Alber, Stefan; Ressel, Wolfram; Canon Falla, Gustavo
Graphical abstract: Highlights: FE models with different aggregate angularities are created. Adhesive fracture at mastic-aggregate interfaces is simulated well by surface-based cohesive behavior. Relationships between aggregate angularity and the mechanical responses are derived. Abstract: Asphalt mixtures are widely used in the construction of high-grade highways and airport pavements. With regard to numerical simulations it was considered as homogeneous due to limitations of low computational capacity. In fact, it is a typical heterogeneous composite material consisting of aggregate with irregular shape and random distribution, asphalt binder and air voids. The heterogeneous numerical model is more consistent with reality and thus yields more reliable results. Experimental investigations have implied that morphological properties of aggregate have a great impact on the performance of asphalt mixtures. Unfortunately, it is extremely difficult to suppress the interferences from other features of the asphalt mixture in experiments, such as aggregate orientations, the spatial distribution of aggregates and air voids. In this study, the microstructural model of asphalt mixture used for uniaxial compression test was reconstructed based on X-ray CT scans, thus maintaining the original morphology of the aggregate. Then the angularity of the aggregate was decreased artificially while the other features of the asphalt mixture remained constant. Based on these microstructures three dimensional finite element models with different aggregate angularities were created followed by a simulation of a uniaxial compression test. The relationship between aggregate angularity and mechanical responses of the asphalt mixture, such as load-carrying capacity, creep deformation of the asphalt mastic, damage behavior and energy dissipation were investigated. The computational results indicate that the aggregate angularity significantly affects the mechanical responses of the asphalt mixture; some initial relationships were set up with high degrees of determination. The quantitative correlation is suggested to be analyzed based on extensive experimental and numerical studies in future research.